THE ROLE OF STRATEGY IN THE ORGANIZATION OF MANAGEMENT IN ENTERPRISES - Izzatullayeva , Madinabonu ("Science Shine" International scientific journal, 2024)
The article highlights that production ravines in industrial enterprises and their management are an extremely complex system, but that managing them with strategy gives great opportunities. Alternatively, as a management backbone, there are ways to choose an alternative strategy for the development of industrial enterprises, as well as an in-depth study of the strategy for achieving the goal.